2015
DOI: 10.1186/s12893-015-0062-9
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative blood loss, postoperative drainage, and recovery in patients undergoing lumbar spinal surgery

Abstract: BackgroundSpine surgery is widely accepted as an effective management for patients with lumbar disc herniation; however, the factors influencing intraoperative procedure and prognosis are not fully understood. The present study was aimed to identify the factors influencing intraoperative blood loss, postoperative drainage volume, and recovery in patients undergoing spinal surgery.MethodsWe retrospectively analyzed the clinical data of 183 consecutive patients with lumbar disc herniation who underwent spine sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 21 publications
1
8
0
Order By: Relevance
“…Indeed, preoperative anemia, together with the amount of perioperative HB drop, were shown to be independent risk factors for increased morbidity, mortality, and longer LOS, with overall increased healthcare costs [ 4 , 6 , 12 , 29 , 30 , 31 , 32 , 33 ]. Thus, the goal for an optimal pre-surgery patient’s preparation would be to detect a condition of anemia or borderline HB levels as early as possible before the scheduled surgery in order to provide correction with treatments directed to increase the RBC mass, i.e., administration of iron, vitamin B12, folic acid, and erythropoietin [ 34 , 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, preoperative anemia, together with the amount of perioperative HB drop, were shown to be independent risk factors for increased morbidity, mortality, and longer LOS, with overall increased healthcare costs [ 4 , 6 , 12 , 29 , 30 , 31 , 32 , 33 ]. Thus, the goal for an optimal pre-surgery patient’s preparation would be to detect a condition of anemia or borderline HB levels as early as possible before the scheduled surgery in order to provide correction with treatments directed to increase the RBC mass, i.e., administration of iron, vitamin B12, folic acid, and erythropoietin [ 34 , 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Total blood loss of 1 to 2 L or more is common and patients are at risk of developing perioperative anemia, which has been shown to increase postoperative morbidity and mortality in a variety of clinical settings. 1-5 Because the mainstay of treatment for blood loss and perioperative anemia is transfusion, the incidence of transfusion in adult spine fusion surgery has been estimated to be as high as 50% to 81%. 6 Advancements in blood testing have markedly improved the safety of allogeneic blood products, but transfusions are not without risks.…”
Section: Introductionmentioning
confidence: 99%
“…8 In addition, Zou et al showed that blood loss in lumbar spine surgery was associated with length of surgery. 12 Our results suggests that operative time was associated with transfusion requirements for both thoracic and lumbar fusion surgeries. Furthermore, thoracic fusion tends to involve more fusion segments, which has also been shown to be an independent factor for requiring blood transfusions.…”
Section: Discussionmentioning
confidence: 61%